Treatment of common bile duct diseases complicated by obstructive jaundice (review) - Sochnieva, Anastasiia Lvovna (Харківський національний медичний університет, 2018)
The article presents the up-to-date data concerning the treatment of common bile duct diseases complicated by obstructive jaundice. Nowadays, specialized clinics widely use mini-invasive interventions to treat this complicated pathology. Biliary tree decompression is the main objective of operative treatment. It is reasonable to perform antegrade and retrograde endobiliary interventions as preparatory and final stages of surgical treatment and in order to improve the patients' life quality and avoid hepatic impairment progression. Reconstructive-reparative operations following prior biliary decompression yield significantly better results as compared to surgical interventions without it.
Keywords: common bile duct diseases; obstructive jaundice; antegrade interventions; retrograde interventions; reconstructive-reparative operations